Phenology patterns across a rupestrian grassland altitudinal gradient - Rocha, Nathália Miranda Walter Bretas [UNESP]; Carstensen, Daniel Wisbech [UNESP]; Fernandes, G. Wilson; Le Stradic, Soizig; Buisson, Elise; Morellato, Leonor Patrícia Cerdeira [UNESP] (Springer Nature, 2016)
Phenology is the study of recurrent biological events in the life cycle of organisms. For plants, reproductive events such as flowering and fruiting are critical stages in their life cycles, which also greatly affect other organisms depending on these resources. Here, we present the first community level plant phenology study across an altitudinal gradient from cerrado through rupestrian grassland to higher altitudinal grasslands developed in the South Espinhaço Mountain range (Serra do Cipó, Brazil). We describe the seasonal patterns of flowering and fruiting phenology and discuss the dependency of reproductive events on the varying climate and habitat types across the gradient. We point out the importance of long-term monitoring and further detailed analyses of families and species contribution to unravel the structure of community phenology, the environmental drivers and sensitivity to climate changes.
Keywords: Altitudinal grasslands; Cerrado; Reproductive phenology; Seasonality patters